-2q-3=-4q-2

Simple and best practice solution for -2q-3=-4q-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2q-3=-4q-2 equation:



-2q-3=-4q-2
We move all terms to the left:
-2q-3-(-4q-2)=0
We get rid of parentheses
-2q+4q+2-3=0
We add all the numbers together, and all the variables
2q-1=0
We move all terms containing q to the left, all other terms to the right
2q=1
q=1/2
q=1/2

See similar equations:

| 2(x-6)-7x=38 | | 5a+2(11.5-4a)=8.5+a | | u^2+14u+49=0 | | 11+3x–7=6x–3x+5 | | 8c−8=7c | | -7(7-3y)=36+4y | | 12+4(2x-1)=16x | | (X/3+5/6)=7x/12 | | -7a−35=-49 | | −7a−35=-49 | | 3x4=67 | | 2x+17=8x-60 | | -4x+11x=35 | | r+48/4=2 | | 6x+5x-45=75+4x | | -5x+19=1/2(6x+8)+2 | | 24+3w=-27 | | 6x+2x=7x-8 | | j+15=26 | | 9x-8=8+7x | | 18−4x=10−2x | | 5−7y=-2y | | 20=1/4x+3 | | f-28=225 | | 5g=3g+6 | | 3a-6=45 | | -2+12x-2=32 | | 7x−3=4x−17x-3=4x-1 | | -6x+2=−5x+5 | | 2(4z-1)=3(z-3) | | 3y+27=-9 | | 27-7x=14+6x |

Equations solver categories